Effects of Digital Media on B2B Sales: An essay on inbound marketing, paid and online media - Corrêa da Silva, Nôga Simões de Arruda (2019)
This theoretical paper suggests a framework that inbound marketing, paid media and online media have effects on the performance of new B2B sales. Previous studies support these effects in an isolated way, not encompassing the variables together that consider their interdependencies (Stephen & Galak, 2012, Opreana & Vinerean, 2015, Hewett et al., 2016, Kumar et al., 2017). Paid online media consists of investments made in keywords on Google and on Facebook. The gained media online comes from shares and comments on social networks. Inbound marketing is a non-intrusive medium based on creating content that generates leads. The theoretical paper brings the following contributions: first, from the theoretical model viewpoint, inbound marketing may be the most proeminent media in explaining new B2B sales, as online paid and earned media may have a direct and indirect influence on sales; second, by classificating the literature, we suggest explanatory and informative tables of the previous results of the inbound marketing, the paid media and the gained online; finally, we propose new paths for future researches in order to prove the theoretical model and the arguments defended in this research.